100k views
1 vote
Use the Binomial Theorem to expand the expression.(x +6)^3

1 Answer

3 votes

ok


\begin{gathered} (x+6)^3=^{}x^3+3(x)^2(6)+3(x)(6)^2+6^3 \\ \text{ = x}^3+18x^2\text{ + 3(36)x + 216} \\ \text{ = x}^3+18x^2\text{ + 108x + 216} \end{gathered}
\begin{gathered} (a+b)^3\text{ } \\ first\text{ term = a} \\ \text{second term = b} \\ \text{theorem } \\ (a+b)^3=a^3+3a^2b+3ab^2+b^3 \end{gathered}

that is the rule

just identify a and b in your problem

a = x

b = 6

Substitute in the theorem, and simplify

User Dross
by
5.3k points